The arctic patrol mystery - Dixon, Franklin W. (Dixon, Franklin W. Hardy boys mystery stories, 1997)
While searching in Iceland for a missing sailor sought by an insurance company, the teen-age detective brothers uncover a plot threatening the life of a United States astronaut and the secrets of NASA's moon project.